Metanalysis of Qualitative and Quantitative improvement in Active Rehabilitation of Post ACL Repair or Reconstruction - Radhika Chintamani (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Physiotherapy regimen is important in both Pre-Surgery and Post-Surgery phases. However, Despite its widespread knowledge of importance of physiotherapy in both pre and post operation phases and during conventional therapy, the efficacy of early active intervention of physiotherapy in post-operative ACL repair/reconstruction is limited on the basis of quantitative and qualitative analysis. Purpose: The aim of this meta-analysis was to analyze the randomized controlled trials having quantitative and qualitative improvement in parameters after active rehabilitation in subjects with post-repair/ reconstruction of Anterior Cruciate Ligament. Methods: The authors searched Google Scholar and PubMed from 2014 to 2019. Only downloadable randomized controlled trials were included in the study. Main results: Twelve trials were included in the study with. The schedule of treatments varied greatly from certain days to 6 weeks or even follow up of 12 weeks. Subgroup analysis performed on Qualitative and quantitative assessment of pre-operative and post-operative active physiotherapy regimen showed significant statistical difference. Conclusion: The result of the present study shows strong evidence to support the active physiotherapeutic treatment pre-operative as well as post-operative in subjects with ACL repair/reconstruction, which helps in improving both qualitative and quantitative parameters.